The solar system : an A-Z guide - Wilsdon, Christina (New York : F. Watts, 2000)
A dictionary of terms, concepts, people, and places related to the solar system, astronomy, and the exploration of space.
Includes bibliographical references (p. 93) and index.
Book Report.
School Library Journal.
Wilson's Children.
6.2
3-6
Keywords: Astronomy -- Dictionaries, Juvenile; Astronomy -- Dictionaries; Astronomy -- Dictionaries